1988
DOI: 10.1525/ae.1988.15.1.02a00020
|View full text |Cite
|
Sign up to set email alerts
|

spirits and selves in Northern Sudan: the cultural therapeutics of possession and trance

Abstract: Examination of cultural and social factors surrounding zar spirit possession diagnoses in Northern Sudan suggests that a major issue addressed by the cult is the cultural overdetermination of women's selfhood. Circumcision and infibulation operate to establish in women a sense of self congruent with the cultural image of woman as reproducer. When experiences and expectations fail to mesh, some women fall ill and are ultimately diagnosed as possessed. Through acceptance of the possession diagnosis and participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(50 citation statements)
references
References 28 publications
1
46
0
3
Order By: Relevance
“…Consequentemente, sob várias abordagens que acompanharam a trilha das grandes escolas que emergiram nas Ciências Sociais ao longo do século passado, o transe de possessão foi perscrutado em termos da satisfação pessoal que provoca e das funções terapêuti-cas que desempenha (Boddy, 1988), como expressão e reflexão individual (Masquelier, 2002) ou coletiva de memórias ou acontecimentos atuais aflitivos (Bairrão, 2004), como meio de resistência velada à subordinação a estruturas de gênero (Brac de la Perrière, 2007), como uma afirmação de exclusividade sobre o atinente ao saber nativo (Van De Port, 2005), ora porta-voz do socialmente desviante ora como mecanismo ativo mantenedor do status quo (Lewis, 1977), ou ainda como drama e performance cultural, fenômeno espetacular legitimado segundo linhas de força articuladas no interior do sistema religioso (Turner, 1988), apenas para mencionar algumas abordagens.…”
Section: Os Primórdios Dos Estudos Sobre a Possessão E O Problema Dosunclassified
“…Consequentemente, sob várias abordagens que acompanharam a trilha das grandes escolas que emergiram nas Ciências Sociais ao longo do século passado, o transe de possessão foi perscrutado em termos da satisfação pessoal que provoca e das funções terapêuti-cas que desempenha (Boddy, 1988), como expressão e reflexão individual (Masquelier, 2002) ou coletiva de memórias ou acontecimentos atuais aflitivos (Bairrão, 2004), como meio de resistência velada à subordinação a estruturas de gênero (Brac de la Perrière, 2007), como uma afirmação de exclusividade sobre o atinente ao saber nativo (Van De Port, 2005), ora porta-voz do socialmente desviante ora como mecanismo ativo mantenedor do status quo (Lewis, 1977), ou ainda como drama e performance cultural, fenômeno espetacular legitimado segundo linhas de força articuladas no interior do sistema religioso (Turner, 1988), apenas para mencionar algumas abordagens.…”
Section: Os Primórdios Dos Estudos Sobre a Possessão E O Problema Dosunclassified
“…Lewis 1971Lewis , 1986Crapanzano 1973) that emphasized problem-solving mechanisms, a more meaning-centred approach focuses on the symbolic, embodied and aesthetic dimensions of spirit possession (Lambek 1981(Lambek , 2003Csordas 1987;Boddy 1989Boddy , 1994Rosenthal 1998;Masquelier 2001). In this framework, the lived-in experiences of spirits are approached as complex cultural statements that express everyday life and enable multiple interpretations of reality (cf.…”
Section: Spirit Spouse Relations As Communicationmentioning
confidence: 99%
“…In this respect, Boddy (1989) considered the role of involvement with spirits in creating awareness and feminist consciousness in her study of women's possession by alien Zar spirits in northern Sudan. She contested Lewis's (1971Lewis's ( , 1986 conclusions that their possession demonstrated that women could not help themselves and needed spirits to resolve their problems.…”
Section: Spirit Spouse Relations As Communicationmentioning
confidence: 99%
“…Boddy, for example, argues that Zar spirit possession in Northern Sudan cannot be understood apart from the local gender dynamics and kinship system within which it is found (Boddy 1988(Boddy , 1993. Women in Northern Sudan are surrounded by symbols and metaphors of idealized femininity that structure their subjective realities and leave little room for the development of an individual with individual self-awareness.…”
Section: The Anthropological-discursive Paradigmmentioning
confidence: 99%
“…Women in Northern Sudan are surrounded by symbols and metaphors of idealized femininity that structure their subjective realities and leave little room for the development of an individual with individual self-awareness. According to Boddy, Zar possession, by widening the context in which a possessed woman operates, opens up pathways for selfrenewal and allows women to move beyond the externally imposed female ideal (Boddy 1988). Furthermore, she argues that "unlike western psychotherapy which encourages the patient to accept and integrate previously dissociated feelings as part of herself, Zar therapy works by convincing her to recognize them as separated from herself in the first place" (1988:20).…”
Section: The Anthropological-discursive Paradigmmentioning
confidence: 99%